Identification of a genome-specific repetitive element in the Gossypium D genome - Hejun Lu; Xinglei Cui; Yanyan Zhao; Richard Odongo Magwanga; Pengcheng Li; Xiaoyan Cai; Zhongli Zhou; Xingxing Wang; Yuling Liu; Yanchao Xu; Yuqing Hou; Renhai Peng; et al. (PeerJ, 2020)
The activity of genome-specific repetitive sequences is the main cause of genome variation between Gossypium A and D genomes. Through comparative analysis of the two genomes, we retrieved a repetitive element termed ICRd motif, which appears frequently in the diploid Gossypium raimondii (D5) genome but rarely in the diploid Gossypium arboreum (A2) genome. We further explored the existence of the ICRd motif in chromosomes of G. raimondii, G. arboreum, and two tetraploid (AADD) cotton species, Gossypium hirsutum and Gossypium barbadense, by fluorescence in situ hybridization (FISH), and observed that the ICRd motif exists in the D5 and D-subgenomes but not in the A2 and A-subgenomes. The ICRd motif comprises two components, a variable tandem repeat (TR) region and a conservative sequence (CS). The two constituents each have hundreds of repeats that evenly distribute across 13 chromosomes of the D5genome. The ICRd motif (and its repeats) was revealed as the common conservative region harbored by ancient Long Terminal Repeat Retrotransposons. Identification and investigation of the ICRd motif promotes the study of A and D genome differences, facilitates research on Gossypium genome evolution, and provides assistance to subgenome identification and genome assembling.